Estándares de desempeño docente - Aimara Guambo, Daniela Judit (2017)
Standards of Teaching Performance is the name of this research is one of the educational sector problem faced today, the teacher must solve to improve their professional work based on the compliance with the teaching standards established by the Ecuadorian Ministry of Education. The standards of teaching performance is a discussion topic in the educational area, which until today has not been able to change the education modality, so that educators do not have the time necessary to attend the courses offered by the Ministry of Education, in terms of teachers´ updating and evaluation, by the deductive, inductive, analytical methods the study is supported in addition to particular methods such as descriptive method and scientific research techniques like the interview with 10 questions which were applied to the directors, teachers and students of the “Ana Páez" Elementary School from Latacunga Cantón reason why the obtained answers by the professionals mentioned above, gave to understand the necessity to be in continuous trainings as long as they are according to their specialty that must be significant so that they can put them into practice in their professional area.